Role Kyai Leadership towards the Independence of Santri through Entrepreneurship at the Galang Sewu Islamic Boarding School - Abdul Malik; Muhammad Fahmi Saifudin; Suryo Ediyono (Genius Journals, 2023)
Kyai Galang Sewu Islamic Boarding School is a boarding school that requires dormitory development. Therefore, Kyaipesantren as the highest leader formed the Songo Team as an auxiliary team for the implementation of development preparations. The results of the joint discussion have raised the idea of forming an entrepreneurial field that functions to support the income of pesantren as well as a vehicle for training the ability of students with entrepreneurial competence. The existence of this entrepreneurship program is because it is also in accordance with the kyai principle which encourages students to live independently mentally, morally and economically. The purpose of this study is to reveal the role of kyai in encouraging student entrepreneurship, Kyai's leadership style in empowering student entrepreneurship, and the implications of entrepreneurship programs on student independence spiritually and materially. This research uses a qualitative approach with a descriptive method. Data collection techniques are carried out by means of interviews, observation, and documentation. The subjects of this study amounted to 5 people. The validity of the data used triangulationsource. Qualitative descriptive data analysis techniques with stages of data collection, data reduction, presentation and conclusions. The results obtained in this study are the role of kyai as caregivers play an active role in directing activities and providing motivation and evaluation as needed. Activities carried out include: cooperatives and washing clothes, raising chickens, catfish cultivation, utilization of empty yards, trainings and processing of agricultural products. The Songo team as the kyai's right-hand man carries out his duties to manage activities according to the objectives and directions of the kyai. Pak Salaf as a kyai also leads with a charismatic and democratic leadership style. The results of entrepreneurial competence are also seen in the person of the students through the visible nature of responsibility for themselves and the fields entrusted to the students
Keywords: Kyai leadership; entrepreneurship; Islamic boarding school